PENGEMBANGAN MEDIA VIDEO ANIMASI UNTUK MATERI PEMBELAJARAN KARAKTER BERSAKSI DI SEKOLAH MINGGU - Denissa Alfiany Luhulima (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2018)
Sunday school is one of the non-formal education for children aged 1-15 years who are Christians in Indonesia, one of them in Maluku. The Sunday SchoolÂ  in Maluku is one of them, under the Maluku Protestant Church (GPM) in the form of Sunday Schools and Tunas Pekabaran Injil (SM-TPI), and also Catechisms. The aim of the GPM Sunday School is to shape the character of GPM children in accordance with the character as written in the Bible; Â but to understand the Bible for children sometimes it is still difficult, because there are several styles of language and thoughts that are quite difficult for children to understand. Therefore, one way to ask children to understand Bible is by applying interesting medial. One of the media that can be used is videos. The types of videos made in this development are animated videos, and the material that is adapted to the Sunday school teaching materials of GPM level 3(9 Years Old), namely testifying character materials. This animated video was developed using the ASSURE research model. The result of the validation tests from material experts, media experts, design experts shows that animated videos are very useful and suitable to be used in the learning process in Sunday school. Based on the results of field tests of this animated video as well, it can help Sunday school children in understanding the material taught by the teacher, particularly the material of testifying characters.Keywords: Sunday school, video, animation